Peningkatan Keterampilan Menulis Puisi Dengan Penerapan Metode Hypnoteaching Pada Siswa Kelas X Di SMAN 1 Bantaeng - Alfiah Darwis; Sitti Rabiah; Ihramsari Akidah (Cetta: Jurnal Ilmu Pendidikan, 2023)
The purpose of this study was to find out how much the students' poetry writing skills increased through the application of the hypnoteaching method in class X MIPA 4 SMAN 1 Bantaeng in learning Indonesian. This type of research is classroom action research (CAR) with quantitative and qualitative analysis techniques using the hypnoteaching method. Based on the results of pre-cycle, cycle I, and cycle II data analysis, it was found that the average class scores obtained by students in learning to write poetry increased. In the pre-cycle, the average class value achieved was 62. In the first cycle, there was an increase in the average value from pre-cycle 11 with the average class value reaching 73. The increase in the average class value also occurred in cycle II, namely the average the class value achieved was 80.25 or an increase from cycle I of 7.25, while an increase from pre-cycle to stage II of cycle was 18.25. Based on the results of this research, it is suggested to Indonesian language and literature teachers to be able to use the hypnoteaching method in learning to write poetry.